2021
DOI: 10.33019/society.v9i1.299
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Analysis of Brand Loyalists and Brand Switcher in 5-Star Accommodation Services in Medan City

Abstract: A brand is a fundamental part of the marketing strategy in influencing purchase interest. A person’s buying ability will influence a customer to choose the product they want. In addition, higher competitiveness among hotels will create more awareness to maintain customer satisfaction and turn it into customer loyalty as the main target of their marketing. In connection with achieving customer loyalty, hotels must study the factors influencing customers to become loyal or switch from the hotel brand. A brand ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Discriminant analysis showed that one factor in need of search change differentiates brand loyalists from brand switchers. The brand transition matrix shows that all hotels in Medan serving consumers have low customer loyalty [3]. Alnsour MS uses a quantitative approach.…”
Section: Introductionmentioning
confidence: 99%
“…Discriminant analysis showed that one factor in need of search change differentiates brand loyalists from brand switchers. The brand transition matrix shows that all hotels in Medan serving consumers have low customer loyalty [3]. Alnsour MS uses a quantitative approach.…”
Section: Introductionmentioning
confidence: 99%